Удосконалення адміністративно-правового регулювання податкової інформації в Україні - Мандзюк, О. А.; Мандзюк, О. А.; Mandzjuk, О. (Одеса : Юрид. л-ра, 2014)
The state and prospects of the legal regulation of tax information in Ukraine. We consider the improvement of state regulation of tax information for ensuring the constitutional right of every citizen to information and protection of the state, which should take into account the changes in the modern world.
Мандзюк О. А. Удосконалення адміністративно-правового регулювання податкової інформації в Україні / О. А. Мандзюк // Актуальні проблеми держави і права: зб. наук.пр. /редкол.: С. В. Ківалов (голов. ред.), В. М. Дрьомін (заст. голов. ред.), Ю. П. Аленін [та ін.]; МОН України, НУ ОЮА. – Одеса: Юрид. л-ра, 2014. – Вип. 71. - С. 67-73.
Keywords: податкове законодавство; механізми податкового регулювання; податкова інформація; нормативно-правове регулювання податкової інформації; налоговое законодательство; механизмы налогового регулирования; налоговая информация; нормативно-правовое регулирование налоговой информации; tax law; tax regulation mechanisms; tax information; legal regulation